O turismo diaspórico como prática de aquilombamento - Gonçalves, Elisa de Paula (Universidade Federal de São Carlos, 2025)
This study explores diasporic tourism as a practice of quilombo formation, analyzing its impact on the reaffirmation of the identity of Black people. Using a qualitative approach, with interviews conducted with Black Brazilians, we investigated how these experiences promote cultural and emotional ties with ancestry, strengthen self-acceptance, and contribute to resistance against structural racism. Diasporic tourism, as a practice of connecting with the roots and communities of the diaspora, reveals itself as a transformative strategy for mental health and the appreciation of Afro-descendant culture. The research seeks to broaden the understanding of the role of tourism in the emancipation and belonging of Black communities.
Diasporic tourism as a practice of quilombola community building
Keywords: turismo diaspórico; aquilombamento; identidade negra; saúde mental; resistência cultural; diasporic tourism; black identity; mental health; CIENCIAS SOCIAIS APLICADAS::TURISMO; 10. Redução das Desigualdades; 3. Saúde e Bem-Estar